The Preparedness of the Indonesian Garment Exporters in the Post-MFA Scenario: An Analysis from the Survey - Muchsin Shihab; Sudhir K. Jain (Gadjah Mada International Journal of Business, 2004)
The clothing or garments industry has developed rapidly during the past some decades and has contributed to the economic growth of many nations, both developed and developing countries. This industry has been very much regulated by many bilateral agreements such as Multi Fiber Arrangement (MFA), a quota arrangement made by the importing countries. As MFA (quota regime) comes to an end by 2005 and integrates into the WTO regime, it will bring opportunities to highly competitive and proactive garment exporting countries whereas the challenges will be faced more by the less competitive countries. Issues related to environment and social compliance, technology requirements etc. have been brought into surface by the importing countries, which may worsen the condition. Under the above scenario, it is imperative that certain proactive measures be taken. Thus, the broad objective of this study is to analyze the response of the garment exporters from Indonesia towards the emerging issues related to environmental and social compliance, technology requirements etc.The present study is a questionnaire-based study. The samples have been selected from the Directories of largest exporters in the country. With reminders and persuasion, the final number of useable responses has been 115 Indonesian garment exporters. Seven factors of the emerging issues were identified by using factor analysis. In addition, factors of competitiveness, and the strategies adopted by the exporters have also been analyzed. The findings show that the overall perceptions of the Indonesia garment exporters indicate that Indonesia is less competitive as compared to other competing countries.